THE STUDENTS’ ADVERSITIES IN MEMORIZING VOCABULARY - Annisa Shofa Tsuraya; Indah Miftah Awaliah; Rezkianti (ELTIES : English Language Teaching for EFL Learners, 2022)
This research aims at finding out the students’ obstacles in memorizing vocabulary due to some factors especially in the aspect of pronunciation and meaning. The researchers investigated the students' difficulties in memorizing vocabulary in one of state universities in Makassar, South Sulawesi. The participant of this study was the third semester students of English Education Department. Qualitative analysis was applied in this research. The researchers collected the data by conducting interviews which then transcribed into a script and documenting several important data that support this research. Based on the data collection, the researcher concludes that the difficulties faced by English students in memorizing vocabulary are; 1) difficulty in utterance 2) difficulty in differentiating the meaning of the words 3) pronunciation problem of the different meaning words but have similar sounds 4) learning words that are not suitable to their needs. Using the dictionary, expressions, and gestures that will help them to boost the vocabulary up easily.